Model Pembelajaran SAVI (Somatic, Auditory, Visualization, dan Intellectually) untuk Meningkatkan Hasil Belajar Siswa - Syifa Kamilah Sophian; Rizka Rifaatul Hidayah; Alay Fia; Dini Safitri; Ade Suryanda (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to examine the effectiveness of the SAVI (Somatic, Auditory, Visualization, and Intellectual) Learning Model in improving student academic performance. The SAVI model combines four key elements—somatic, auditory, visual, and intellectual—allowing students to learn actively and engage fully in the learning process. This approach not only creates variation in teaching methods but also helps students find learning methods that align with their individual learning styles. Through this structured approach, students are given the opportunity to develop their understanding through hands-on experiences, listening to explanations, seeing visual representations, and engaging in critical thinking activities. This research utilizes a literature study method to explore the effectiveness and applications of the SAVI Model. The findings reveal that implementing this model increases student motivation, promotes their engagement in class, and strengthens their understanding of learned concepts. Moreover, the model plays a crucial role in honing students’ critical thinking, communication, and collaboration skills, which are essential competencies for student development in the modern era.